Comparative study an effect of polymethyl methacrylate coating on optical microbottle resonator for enhancing sensing performance for ethanol liquid sensor - Yasin, Mohammad; Md Johari, Md Ashadi; Apsari, Retna (John Wiley and Sons Inc., 2023)
This paper observed the performance of the coated optical microbottle resonator (MBR) for the liquid ethanol concentration sensor. The MBR is prepared in three sizes by a technique known as “soften‐and‐compress” from silica fiber SMF‐28 with parameters named stem diameter, bottle length, and bottle diameter. The MBR is then coated with PMMA by the “drop‐casting” technique used as an ethanol sensor. The MBR‐PMMAs were characterized by microfiber diameter and managed to have a Q‐factor. The ethanol liquid concentration used is from 10% to 100% ppm. The sensitivity, linearity, repeatability, stability, and wavelength shift results were then used to determine the performance of MBR‐PMMAs as an ethanol sensor. The most significant size of MBR‐PMMA, known as “C,” is defined as an excellent ethanol liquid concentration sensor. Additionally, the resonator's size is determined and may influence its ability to perform well as a sensor.